2015
DOI: 10.1007/s11998-014-9643-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyglycerol as an additive for water-based printing ink

Abstract: In this work, the application of hyperbranched polyglycerol as a performance additive for water-based printing inks is demonstrated. The hyperbranched polyglycerol, (BPG), was synthesized through anionic ring-opening polymerization from glycidol using 1-butanol as the starting material. The branched structure of BPG is presented and described. The presence of linear, dendritic and terminal units was confirmed by Moore et al. (Prog Surf Sci 88(3):213-236, 2013) 13 C NMR spectroscopy. BPG was then used as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…The absorption bands at 3400 cm -1 , 2900 cm -1 and 1100 cm -1 are associated with the peripheral hydroxyl groups (OH), aliphatic C-H and ether (C-O-C) stretching bands of PGLyD microspheres, respectively, which is in good agreement with the literature values 23 Water bonding at 1650 cm -1 and O-H stretching broad band centered at 3500 cm -1 suggests the presence of water of crystallization 24 . From the above discussion it was confirmed that microencapsulation of CoHo into PGLyD shell had been successfully performed.…”
Section: Coho:pglyd Preparation and Characterizationsupporting
confidence: 89%
“…The absorption bands at 3400 cm -1 , 2900 cm -1 and 1100 cm -1 are associated with the peripheral hydroxyl groups (OH), aliphatic C-H and ether (C-O-C) stretching bands of PGLyD microspheres, respectively, which is in good agreement with the literature values 23 Water bonding at 1650 cm -1 and O-H stretching broad band centered at 3500 cm -1 suggests the presence of water of crystallization 24 . From the above discussion it was confirmed that microencapsulation of CoHo into PGLyD shell had been successfully performed.…”
Section: Coho:pglyd Preparation and Characterizationsupporting
confidence: 89%
“…Our previous work shows that branched glycerols have a positive effect on the wettability, the adhesion, and wet or dry rub resistance. 18,26,27 Ink properties Before printing, the selected properties of the printing ink were estimated: the wettability of the printing base by the ink (by measuring the contact angle of printing ink on the various plastic films) and surface tension (pendant drop method).…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%
“…Note that local regulations impose certain degrees of polymerization to the food industry; for instance, according to the EU law, PGs for food applications should not contain polymers containing more than seven condensed glycerol molecules (PG7) [2]. In contrast, PG2-PG10 have the U.S. Food and Drug Administration (FDA) approval [23]. Linear polyglycerols are known as being structurally similar to polyethylene glycol (PEG), which is produced from petrol-sourced ethylene oxide.…”
Section: Name (Abbreviation)mentioning
confidence: 99%
“…For instance, hyperbranched polyglycerols have already found applications as surfactants in the plastic industry for treating lithographic printing plates and as organic solvents in aqueous inkjet-printing inks to prevent paper deformation. HBPGs can also be used as performance additives in water-based printing inks due to their higher solubility in water compared to polyesters [13,23].…”
Section: Name (Abbreviation)mentioning
confidence: 99%